The Effect of Hydrolyzed Pectin as a Sugar Substitute on The Physicochemical Properties of Pineapple Spread - Lo, Diana; Michellina, Michellina; Tedjakusuma, Felicia; Huang, Cian-Song (Green Engineering Society, 2023)
Pineapple is a fruit that is widely produced in Indonesia. Pineapple can be processed into jam or fruit spread to extend its shelf life. However, jam contains high amount of sugar. High consumption of sugar in the diet can contribute to a high kilojoules diet or known as 'energy dense' and thus contribute to the development of health problems like obesity or diabetes. Sugar has important role in the jam. It binds water molecules to build spreadable product. Pectin can also bind water molecules and cannot be digested by human body but addition of pectin as sugar replacement cannot build spreadable product because pectin molecules is much longer than sucrose. Thus, depolymerization through hydrolysis is needed on pectin molecule. Therefore, the purpose of this research was to determine the effect of different hydrolyzed pectins as substitute for sucrose in a pineapple spread. The physicochemical properties of hydrolyzed pectin (viscosity and color value) and pineapple spreads made from the hydrolyzed pectin (color value, degree of brix, water activity, syneresis and spreadability) were investigated. The results showed that pectin treated with 0.05 M of HCl for 96 h produced the best pineapple spreads based on water activity and percentage of syneresis results. Moreover, pineapple spreads made from pectin treated with 0.05 M of HCl for 96 h has the most similar color and spreadability to the one with sucrose.